Monitoring time-varying noise levels and perceived noisiness in hospital lobbies. Issue 1 (March 2021) - Chen, Chiung Yao
The aim of this study was to verify what statistical attributes are effective descriptors of time-varying noise levels due to road traffic and complex medical routine activities in hospital lobbies. In a psychoacoustic experiment, respondents provided perceived noisiness ratings affected by 12 noise events in hospital lobbies according to the processes recommended by ISO 15666. According to the correlations between subjective and objective survey results, the average LAeq, 15 m induced during the daytime itself was confirmed to be poorly related to subjective noisiness. The three independent variables shown to have the largest effects on perceived noisiness were (1) L min − L max, (2) the effective duration of the normalized autocorrelation function ( τe, h) of all LAeq, 15 m from 9:00 a.m. to 5:00 p.m., and (3) the gradient of the cumulative distribution function (0.3–0.7 cumulative rate range). These statistical attributes have been confirmed as useful tools for detecting perceptions of complicated noise sources, but the associated correlations cannot be recovered from the relevant previous studies. Finally, construction noise was confirmed by factor analysis to be the accidental noise source with the highest factor loading (0.779) but a lower variance (<11.5%) than that of the primary factor (38.6%), and it was an average of 8 dB louder than the background noise at any given time. Accordingly, it is a primary confounding variable of the correlation matrixes of the results for independent hospitals verified by normality test.